Emergency and critical care: top tips for your survival!. Issue 6 (3rd June 2017) - Pointer, Sarah
Abstract: Emergency situations are relatively commonplace in the veterinary practice, and as such are linked in with the RCVS Day One competencies. Student veterinary nurses have always had an element of emergency nursing included in their training. Good teamwork, communication and preparation are key factors in the successful resolution of the emergent case. An appropriate framework should be followed during the triage process, which identifies the main issues and considerations in the critical patient. The use of monitoring equipment is vital during this period, and veterinary staff should endeavour to be familiar with its use to gain most value from the information it provides.